Tardive dyskinesia in Asia— current clinical practice and the role of neurologists in the care pathway - Bhidayasiri, Roongroj; Phokaewvarangkul, Onanong; Shang, Hui-Fang; Lim, Thien Thien; Cho, Jin Whan; Pal, Pramod Kumar; Watanabe, Hirohisa (Frontiers in Neurology, 2024)
Tardive dyskinesia (TD) is a movement disorder that can arise as a side effect of treatment with dopamine receptor-blocking agents (DRBAs), including antipsychotic drugs (APDs) used to manage psychotic illnesses. Second-generation APDs (SGAs) are often preferred to first-generation drugs due to their lower propensity to cause TD, however many SGAs-treated patients still develop the condition. Although TD is a global health concern, evidence regarding the occurrence of TD and how it is managed in Asian countries is currently limited. This article reports the results of a systematic review of the published literature on TD focusing on its prevalence, types of patients, knowledge of the condition, causative factors, and usual treatment pathways in clinical practice in Asian countries. Epidemiological data suggest that the prevalence of TD is increasing globally due to an overall rise in APD use, contributing factors being polypharmacy with multiple APDs, the use of higher than necessary doses, and off-label use for non-psychotic indications. Although exact prevalence figures for TD in Asian countries are difficult to define, there is a similar pattern of rising APD use which will result in increasing numbers of TD patients in this region. These issues need to be addressed and strategies developed to minimize TD risk and manage this disabling condition which impacts patients' quality of life and daily functioning. To date, both research into TD has been predominantly psychiatry focused and the perspectives from neurologists regarding the clinical management of this challenging condition are scarce. However, neurologists have an essential role in managing the movement disorders manifestations that characterize TD. Optimum management of TD, therefore, should ideally involve collaboration between psychiatrists and neurologists in joint care pathways, wherever practical. Collaborative pathways are proposed in this article, and the challenges that will need to be addressed in Asian countries to improve the care of people with TD are highlighted, with a focus on the neurologist's viewpoint and the implications for the management of TD globally.